Dillapiole-Rich Piper aduncum L.: Phytochemistry, Bioactivity, and Pharmaceutical Applications – A Systematic Review - Yahya Febrianto; Erindyah Retno Wikantyasning; Ratna Yuliana (UNIVERSITAS PGRI MADIUN, 2026)
The growing interest in the development of phytopharmaceuticals derived from traditional medicinal plants has driven in-depth exploration of Piper aduncum L., a species with diverse therapeutic potential that has not yet been systematically consolidated. This systematic review aims to identify, analyze, and synthesize recent scientific evidence regarding the phytochemical constituents, pharmacological activities, and pharmaceutical development prospects of P. aduncum based on publications from 2021 to 2025. The study adopted the PRISMA 2020 framework, conducting a comprehensive search across five electronic databases using a combination of keywords related to the phytochemistry and pharmacology of P. aduncum. Literature selection was performed through three stages, resulting in six articles that met the inclusion criteria, consisting of two in vivo studies, three laboratory experimental studies, and one systematic review. Methodological quality assessment was conducted using the Modified Downs and Black Checklist and the SYRCLE’s Risk of Bias Tool, followed by systematic data extraction and qualitative narrative synthesis. The findings indicate that dillapiole is the predominant component of the essential oil, with concentrations ranging from 77.6–85.5%, exhibiting antiparasitic, acaricidal, antimycobacterial, immunomodulatory, and anti-inflammatory activities through mechanisms involving modulation of detoxification enzymes and intestinal microbiota. The development of nanocarrier systems has produced stable nanometric formulations with an excellent safety profile for topical applications. This review confirms the significant potential of P. aduncum as a candidate for the development of biopesticides, alternative antimicrobial agents, and phytogenic feed additives. However, further translational research is required, including extraction standardization, investigation of molecular mechanisms, pharmacokinetic–pharmacodynamic studies, long-term toxicological evaluation, and clinical trials to validate efficacy and safety prior to therapeutic application in humans.